Shaming and Sanitation in Indonesia: A Return to Colonial Public Health Practices?. Issue 1 (January 2014) - Engel, Susan; Susilo, Anggun
ABSTRACT Adequate sanitation is vital to human health, yet progress on the Millennium Development Goal for sanitation has been slow and the target is likely to be missed by one billion people. Indonesia has the third highest number of people of any country in the world without access to sanitation and, like most developing countries, it is devoting insufficient resources to the issue. In rural areas, rather than providing additional funding, the government — with support of the World Bank — has promoted the Community‐Led Total Sanitation (CLTS) approach, which uses social mobilization to encourage people to construct their own latrines. In Indonesia as elsewhere, CLTS involves more than just education and encouragement; it uses social shaming and punishments. The authors argue that this is not only an inadequate approach but one which echoes coercive, race‐based colonial public health practices. This article thus integrates extant historiography on Indonesian colonial medicine with contemporary scholarly literature and field research on CLTS using case studies of a 1920s hookworm‐eradication programme funded by the Rockefeller Foundation, and the current World Bank Water and Sanitation Programme, both in Java.